ANALISIS FUNGSI PEMILU DAN TUJUAN PARTAI POLITIK DALAM HUKUM TATA NEGARA - Hendrawati, Sulkiah (LPPM Universitas Bina Bangsa, 2024)
In the science of constitutional law, general elections are one way of filling positions to elect representatives of the people in a democratic state. In other words, the object of study of constitutional law as a law that regulates the organization of the state and how to run the government, according to Maurice Duverger, includes the issue of how the people exercise constitutional rights, such as the system of representation in the state, the electoral system, parliament, ministers, head of government (chief de l'Etat), etc. The implementation of elections is a very important momentum for the formation of government and the administration of the state for the next period. The importance of periodic elections is due to several reasons. First, the opinions or aspirations of the people regarding various aspects of common life in society are dynamic, and develop from time to time. Secondly, the conditions of life together in society can change, both because of the dynamics of the international world and because of domestic factors. Third, changes in the aspirations and opinions of the people can also be possible due to the increase in the number of adult population/people as new voters